On the Numerical Solution of Nonlinear System of Coupled Sine-Gordon Equations - Yildirim, Ozgur; Uzun, Meltem; Altun, Oguz (AMER INST PHYSICS, 2018)
In this paper, a system of nonlinear coupled sine-Gordon, which have some powerful applications in physics and biology is considered. A special case of this system, which describe the open states in DNA double helices is studied. Numerical solution of this system is obtained by finite difference method with fixed point iteration. Some examples are considered and the results of numerical experiments are presented.
Keywords: DIFFERENCE-SCHEMES; HIGH-ORDER; Mathematics; Physics